Design and fabrication of garden storage tool cart / Muhammad Akmal Syahmi Sazaleigh - Sazaleigh, Muhammad Akmal Syahmi (2023)
"Design and Fabrication of Garden Storage Tool Cart" is the title of this project. The goal of this project is to assist people who enjoy gardening in their backyards and small gardens in reducing the burden and back pain while gardening. This is because the main issue that these people face is that they use more energy, which can cause serious back pain, especially for the elderly who enjoy gardening. This project's goal is to fabricate and modify an existing storage box into a rolling garden storage box with a seater. Following that, determine the maximum applied load, focusing on a seater that can be accommodated by the storage gardening tool cart. This project will also include design, fabrication, and analysis. This project will be designed using the 3D engineering software "Solidworks 2019." In this project, there are some calculations that use the Strength of Material equation to calculate bending stress and force.